Involvement of the leptin-adiponectin axis in inflammation and oxidative stress in the metabolic syndrome - Frühbeck, Gema (Sci Rep, 2017)
The aim of the present work was to study whether the leptin-adiponectin axis may have a pathophysiological role in the increased systemic inflammation and oxidative stress observed in patients with the metabolic syndrome (MS). Leptin, adiponectin, and markers of inflammation and oxidative stress were measured in a sample of 140 Caucasian subjects (74 males/66 females), aged 28–82 years, 60 with and 80 without the MS. Total concentrations of adiponectin as well as its multimeric forms HMW, MMW and LMW were significantly lower in individuals with the MS. The ratio adiponectin/leptin, a marker of dysfunctional adipose tissue, was dramatically decreased in the MS group. Systemic oxidative stress, as evidenced by levels of thiobarbituric acid reactive substances (TBARS), as well as markers of inflammation such as serum amyloid A (SAA), C-reactive protein (CRP) and osteopontin were significantly increased in subjects with the MS. Total adiponectin concentrations were negatively correlated with levels of TBARS and CRP levels. Furthermore, the ratio adiponectin/leptin was negatively correlated with SAA concentrations as well as with CRP levels. We concluded that a dysfunctional adipose tissue as suggested by a low adiponectin/leptin ratio may contribute to the increased oxidative stress and inflammation, hallmarks of the MS.